Interaksi Guru dan Siswa Pada Pembelajaran Akhlak Akhlak di SD IT Tahfizhul Qur’an Miftahul Jannah - Husna, Hafiza; Anngraini, Sri Veronica; Ariani A, Rini (Yayasan Rahmat Islamiyah, 2024)
The teaching of Islamic morals and ethics in Islamic religious schools involves not only conceptual understanding but also dynamic interaction between teachers and students. This study explores the dynamics of this interaction at SD Tahfizhul Jannah Medan through a qualitative approach using interview and participatory observation methods with teachers and students in Islamic morals and ethics classes. The results indicate the significant role of teacher-student interaction in shaping students' character and morals, as well as the teacher's role as a living example in applying Islamic values. Although it strengthens understanding of Islamic concepts and student motivation, challenges also arise, such as differences in understanding and constraints in applying moral values in the context of modern life. This research provides insights into how teacher-student interaction influences the teaching of Islamic morals and ethics in Islamic religious schools, and its implications for the development of more effective curriculum and teaching practices.